USE OF SMARTPHONE AND VIRTUAL REALITY AND AUGMENTED REALITY GLASSES IN MATHEMATICS CLASSES - Andrade, Emanuel Adeilton O.; de Assis de Oliveira Andrade, Francisco; Gregório Antunes de Medeiros, Ismaelita (Journal of Interdisciplinary Debates, 2021)
The present work presents a research carried out with 6th and 7th grade students of Elementary School II at Escola Municipal Mon. Walfredo Gurgel Alto do Rodrigues/RN, aiming to encourage the use of materials such as Ruler and Square in Mathematics classes and to know your opinion about the use of Augmented Reality and Virtual Reality glasses. This aimed at a reflective analysis of how the inclusion of technologies in education can enhance learning when the use of multimedia resources that help in understanding mathematical concepts or that enable a dynamic visualization of the object of study are encouraged. She seeks to know what the contribution of this device to the teaching and learning process of Mathematics. Methodologically, the work is characterized as an exploratory research of qualitative and quantitative nature, with a bias towards a case study, with data collected through a semi-structured questionnaire with 102 students. We can count on an interdisciplinary planning to present the programmed contents with more meaning. The results were analyzed based on the research instruments and the testimonies of the students, in addition to a brief study on information and communication technologies applied to learning. Thus, the data are organized in graphs where the research findings are expressed.